First class : the U.S. Postal Service, democracy, and the corporate threat - Shaw, Christopher W. (Open Media book., 2021)
"The U.S. Postal System is under assault. For decades, corporate interests and ideologues have sought to convert this invaluable public institution into yet another profit-driven corporation. In 2020, the attacks escalated. In the middle of a pandemic and a presidential election dependent on mail-in ballots, the newly installed postmaster, Louis DeJoy, disrupted postal operations by slowing down mail delivery, decreasing window hours, and removing mail-processing equipment and neighborhood mailboxes. An outraged and indignant public fought back and scored a victory, reversing his policies. Though that stage of the battle ended in a public victory, the corporate war against the Postal System continues. In First Class, Christopher Shaw provides a brief history of the USPS, exposing the various campaigns against it, who has been waging them, and the consequences to the American public--and democracy itself--if they are not stopped"--